2008
DOI: 10.1523/jneurosci.1885-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Convergence of Dopaminergic and Cholinergic Input Is Critical for Hippocampus-Dependent Working Memory

Abstract: Although Parkinson's disease is a movement disorder, in many patients cognitive dysfunction is an important clinical sign. It is not yet clear whether this is attributable solely to a decrease in dopamine levels, or whether other neurotransmitter systems might be involved as well. In the present study, the importance of the mesocorticolimbic dopamine pathway and a possible convergence with forebrain cholinergic projections to neocortex and hippocampus in the regulation of learning and memory abilities were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 64 publications
4
41
1
Order By: Relevance
“…Alternatively, the LS-C41821 ChAT antibody was also used on rat tissue because of a better signal-to-noise ratio. Characterized by Crawford et al (66), the LS-C41821 ChAT antibody is routinely used to label cholinergic neurons in the rat brain (67,68). The labeling obtained with this antibody was very similar to that obtained with AB144P.…”
Section: Methodsmentioning
confidence: 72%
“…Alternatively, the LS-C41821 ChAT antibody was also used on rat tissue because of a better signal-to-noise ratio. Characterized by Crawford et al (66), the LS-C41821 ChAT antibody is routinely used to label cholinergic neurons in the rat brain (67,68). The labeling obtained with this antibody was very similar to that obtained with AB144P.…”
Section: Methodsmentioning
confidence: 72%
“…This has implications for how we may interpret data from studies that look at the impact of mDA loss at the level of the hippocampus. For example, reduced neurogenesis (Suzuki et al, 2010) or deficits in cognitive function (Wisman et al, 2008) after 6OHDA lesioning may reflect mechanisms that are more indirect than loss of a direct mDA-hippocampus pathway -i.e., changes in hippocampal signaling at a broader systems level involving dopaminergic innervation of other nuclei that feed forward to the hippocampus. Both the nucleus accumbens and amygdala may be interesting targets to investigate further in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that loss of midbrain dopamine (mDA) neurons in the rodent brain results in a reduction in hippocampal cell proliferation and neurogenesis (Suzuki et al, 2010),and can also impair cognitive function (Wisman et al, 2008). Interestingly, the rate of hippocampal neurogenesis has been shown to decline sharply with age (Ben Abdallah et al, 2010;Spalding et al, 2013)with a concomitant cognitive decline, and this is thought to be part of the pathophysiological basis of age-related dementia (Drapeau et al, 2003;Small et al, 2011;Seib et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The MWM was described in previous studies (Andringa et al, 2000;Wisman et al, 2008). Briefly, the pool dimensions were a diameter of 185 cm and a water depth of 30 cm, and the water temperature was 21° Celsius.…”
Section: Morris Water Maze (Mwm)mentioning
confidence: 99%